Pelatihan Penyusunan Laporan Keuangan Pesantren Berdasar Pedoman Akuntansi Pesantren - Rakhmawati, Ita; Nuha, Ulin; Suparwi; Purwati (Jurnal Pemberdayaan Masyarakat, 2024)
This service activity focuses on training in preparing financial reports for pesantren in Kudus using the Pesantren  Accounting Guidelines. The absence of financial management (accounting) expertise among administrative staff in pesantren and the shortage of financial administration personnel are issues faced by aided partners. On the other hand, pesantren are still unfamiliar with the requirements and expectations of compiling financial reports due to the government's lack of socialization over the pesantren accounting guidelines. The approach used in this service is community development practice, a community service methodology founded on community and maximizing available resources to establish long-term continuity, is the strategy employed in this service. Accompanied partners include thirteen pesantren and Rabithah Maahid Islamiyah Kudus Regency.  The result of this service is the awakening of awareness of the importance of preparing financial reports for pesantren entities; increasing the competency of Islamic boarding school financial administration staff in the field of accounting, increasing the ability of pesantren in preparing financial reports including net asset change statement, cash flow statement and also financial position statement.